Preoperative prognostic factors for 5-year survival following pulmonary metastasectomy from colorectal cancer: a systematic review and meta-analysis. (21st February 2023) - Gkikas, Andreas; Kakos, Christos; Lampridis, Savvas; Godolphin, Peter J; Patrini, Davide
Abstract: OBJECTIVES: We seek to identify preoperative prognostic factors and measure their effect on 5-year survival following pulmonary metastasectomy (PM) for Colorectal Cancer (CRC). METHODS: We systematically reviewed the databases of Cochrane Library, MEDLINE, Embase and Google Scholar from January 2000 to April 2021 to identify preoperative factors that have been investigated for their prognostic effect on survival following PM. Quality assessment was performed using the QUIPS tool. The prognostic effect of each identified factor on 5-year survival post-PM was estimated using random-effects meta-analyses. RESULTS: We identified 115 eligible articles which included 13 294 patients who underwent PM from CRC. The overall 5-year survival after resection of the lung metastasis was 54.1%. The risk of bias of the included studies was at least moderate in 93% (107/115). Seventy-seven preoperative factors had been investigated for their prognostic effect. Our analysis showed that 11 factors had favourable and statistically significant prognostic effect on 5-year survival post-PM. These included solitary metastasis, size <2 cm, unilateral location, N0 thoracic disease, no history of extra-thoracic or liver metastasis, normal carcinoembryonic antigen levels both before PM and CRC excision, no neo-adjuvant chemotherapy before PM, CRC T-stage < T4 and no p53 mutations on CRC. Disease-free interval at 24 months did not appear to affect 5-year survival. CONCLUSIONS: Despite the considerable risk of bias in the literature, our study consolidates the available evidence on preoperative prognostic factors for PM from CRC. These findings can complement both clinical practice and the design of future research on the field of PM. Abstract : Pulmonary metastasectomy (PM) is a widely performed procedure offered to patients with lung metastases and has been described as a 'pillar of modern thoracic surgery' [1, 2].